2003
DOI: 10.1002/ceat.200301848
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mixing Quality in Micromixers

Abstract: The laminar flow patterns and mixing performance of two different micromixers have been investigated and quantified using CFD. The micromixer geometries consist of a channel with either diagonal or asymmetric herringbone grooves on the channel floor. The numerical results show that a single helical flow is produced for the diagonal mixer, whereas the herringbone mixer creates a double helical flow, composed of an alternating large and small vortex. Particle tracking of a tracer shows that very little convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 19 publications
4
90
0
1
Order By: Relevance
“…Furthermore, it is evident that at the same groove depth, a much smaller L m value is needed for the SHM than the SGM, confirming that mixing within the SHM is more effective and faster than that within the SGM. This is consistent with reported simulation and experimental results [11,12]. …”
Section: Comparisons Between Sgm and Shmsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, it is evident that at the same groove depth, a much smaller L m value is needed for the SHM than the SGM, confirming that mixing within the SHM is more effective and faster than that within the SGM. This is consistent with reported simulation and experimental results [11,12]. …”
Section: Comparisons Between Sgm and Shmsupporting
confidence: 93%
“…Stroock et al [11] studied the mixing in both staggered herringbone micromixers (SHM) and slanted groove micromixers (SGM) at low Re and showed that mixing could be enhanced by using herringbone shaped asymmetric structures on the floor of the channel. Two counter-rotating vortices were found in the channels of SHM in a study by Aubin et al [12], in which a computational fluid dynamics (CFD) was also used for simulation. Kim et al [13] presented a chaotic micromixer, in which chaotic mixing was achieved by periodic perturbation of a helical type of flow obtained by slanted grooves.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Another greatly efficient passive mixer is the one that uses chaos due to the complexity of the conduct channels such as: herringbone groove channel (5), (6) , or C-shaped serpentine channel developed by Liu et al (7) . Passive mixers have advantage in term of easily installing into an integrated device.…”
Section: Introductionmentioning
confidence: 99%